Peran Metode Kitabah Dalam Pengembangan Keterampilan Hafalan Santri di Rumah Tahfidz Al Falah: Peran Metode Kitabah Dalam Pengembangan Keterampilan Hafalan Santri di Rumah Tahfidz Al Falah - Ariani, Farida; Fitri, Aulia; Hankam, Arief Arafat; Reflianto, Reflianto; Amris, Firda Khairati; Afnita, Nora (Journal of Humanity Dedication, 2024)
Method in the process of learning the Qur'an. This community service aims to explore the impact of using the kitabah method on the memorization skills of the students. The community service applies a community-based research method, conducting community research to improve Qur'anic reading skills using the kitabah method. The assistance activities include improving the quality of the students' memorization and understanding of the verses through several steps. First, students must understand tajweed and the pronunciation of letters. The memorization is written repeatedly with a focus on accuracy, and students read their writings repeatedly to reinforce memory through visual and motor activities. The results of the assistance show a significant improvement in the students' tahsin and tahfiz skills. This method is very effective in accelerating pronunciation, tajweed, and memorization abilities. This activity has made a positive contribution to the students in enhancing their tajweed skills and Qur'anic memorization. Keywords: kitabah method, skill development, student memorization